Implementasi Kurikulum Merdeka terhadap Peningkatan Minat Belajar Siswa SMA Negeri 3 Sumbawa - Parhun, Muhammad; Junaidi, Muahammad (FONDATIA, 2025)
This study aims to analyze the implementation of Merdeka Curriculum and its impact on increasing students' interest in learning class X. Merdeka 1 in the subject of Islamic Religious Education (PAI) at SMA Negeri 3 Sumbawa Besar. The Merdeka Curriculum is a new policy in the Indonesian education system that encourages more contextual, fun, and student-centered learning. This research used a qualitative approach with a case study method. Data collection was carried out through learning observations, interviews with PAI teachers, students, and school officials, and study of related documents. The results showed that the implementation of Merdeka Curriculum at SMA Negeri 3 Sumbawa Besar was carried out in stages, including socialization, teacher training, and preparation of learning tools. PAI learning with the Merdeka Curriculum uses varied methods, such as project-based learning, group discussions, and contextual learning, as well as utilizing information technology media and authentic learning resources. After the implementation of Merdeka Curriculum, there is an increase in students' interest in learning PAI subjects, which can be seen from students' enthusiasm and activeness in learning, increased learning motivation, ability to relate material to real life, creativity in completing projects, and comprehensive authentic assessment. Factors that influence the increase in student interest in learning include teacher readiness, supporting facilities and infrastructure, a conducive learning environment, innovative learning approaches, and student characteristics.